Beta diversities of grassland birds indicate the importance of pastoralism for nature conservation of the Qinghai–Tibetan plateau - Li, Li; Tietze, Dieter Thomas; Fritz, Andreas; Basile, Marco; Lü, Zhi; Storch, Ilse (Frontiers in Conservation Science, 2022)
Multifunctionality of agricultural landscapes is becoming prominent for nature conservation under the post-2020 global biodiversity framework. The key challenge, however, is to unveil ecological processes that underpin the synergy of the production and conservation functions of agricultural landscapes. The eastern Qinghai-Tibetan Plateau (QTP) is an important hotspot of endemic birds in Asia. Meanwhile, it is one of the world’s largest livestock grazing systems sustaining a stocking rate of over 22 million sheep units. To inform conservation planning, our research aims to investigate the impact of livestock grazing on alpine bird assemblages at the local scale (alpha diversity) and their variation across the pastoral landscape (beta diversity). In the study area Nyanpo Yutse, we conducted bird surveys of 126 bird sample plots during two breeding seasons to acquire bird assemblage data. Meanwhile, we employed unmanned aerial vehicles to measure 2D and 3D habitat features at the 150-m radius. We investigated the key habitat variables driving the spatial distributions of both alpha and beta diversities of birds. Particularly, we partitioned beta diversity into its turnover and nestedness components and tested their patterns across sites of four levels of livestock grazing intensities (LGIs). Our results found no significant correlation between LGIs with species richness of birds, while 2D, 3D habitat complexity and anthropogenic element cover were positively correlated with alpha diversity (p < 0.05). At the landscape scale, pairwise LGI differences had no significant correlation (p > 0.05) with any pairwise beta diversity. The ordination plotting of 12 common birds and 8 endemic birds showed that species had specific and different habitat preferences. The multiple-site beta diversity of the 126 plots showed high species turnover (> 0.871) where LGI was lower than 1.065 sheep unit/ha, indicating the importance of protecting moderately grazed landscape in the eastern QTP. Our study demonstrated that extensive pastoralism is important for maintaining the mosaic landscape. Besides, anthropogenic structures contributed to the increase in habitat vertical complexity from which keystone structures emerge. As such, we unveiled one of the ecological mechanisms through which synergy between agricultural production and biodiversity conservation in the Tibetan livestock grazing system can be realized.